Land Case Mediation at BPN as a Form of National Land Law Development - Br Sembiring, Novira (Jurnal Smart Hukum (JSH), 2025)
One of the most significant obstacles to the advancement of national land legislation is the resolution of land disputes. This article seeks to analyze the role that mediation plays as a means of resolving land disputes when implemented by the National Land Agency (BPN), with the aim of supporting the development of a more just and sustainable land law. This research employs a qualitative methodology, with the analysis of data pertaining to mediation cases administered by the BPN in multiple regions. The findings indicate that mediation proves an effective method of resolving land-related disputes through a peaceful resolution, despite the existence of obstacles, namely the low level of participation by some parties and the restricted resources of the BPN itself. The study ultimately concludes that, with the implementation of more robust policies and the enhancement of institutional capabilities, mediation has the potential to provide substantial support in the advancement of national land law development.